Catabolic cytokines disrupt the circadian clock and the expression of clock-controlled genes in cartilage via an NFкB-dependent pathway. Issue 11 (November 2015) - Guo, B.; Yang, N.; Borysiewicz, E.; Dudek, M.; Williams, J.L.; Li, J.; Maywood, E.S.; Adamson, A.; Hastings, M.H.; Bateman, J.F.; White, M.R.H.; Boot-Handford, R.P.; et al.
Summary: Objective: To define how the catabolic cytokines (Interleukin 1 (IL-1) and tumor necrosis factor alpha (TNFα)) affect the circadian clock mechanism and the expression of clock-controlled catabolic genes within cartilage, and to identify the downstream pathways linking the cytokines to the molecular clock within chondrocytes. Methods: Ex vivo cartilage explants were isolated from the Cry1 -luc or PER2::LUC clock reporter mice. Clock gene dynamics were monitored in real-time by bioluminescence photon counting. Gene expression changes were studied by qRT-PCR. Functional luc assays were used to study the function of the core Clock/BMAL1 complex in SW-1353 cells. NFкB pathway inhibitor and fluorescence live-imaging of cartilage were performed to study the underlying mechanisms. Results: Exposure to IL-1β severely disrupted circadian gene expression rhythms in cartilage. This effect was reversed by an anti-inflammatory drug dexamethasone, but not by other clock synchronizing agents. Circadian disruption mediated by IL-1β was accompanied by disregulated expression of endogenous clock genes and clock-controlled catabolic pathways. Mechanistically, NFкB signalling was involved in the effect of IL-1β on the cartilage clock in part through functional interference with the core Clock/BMAL1 complex. In contrast, TNFα had little impact on the circadian rhythm and clock gene expression in cartilage. Conclusion: In our experimental system (young healthy mouse cartilage), we demonstrate that IL-1β (but not TNFα) abolishes circadian rhythms in Cry1 -luc and PER2::LUC gene expression. These data implicate disruption of the chondrocyte clock as a novel aspect of the catabolic responses of cartilage to pro-inflammatory cytokines, and provide an additional mechanism for how chronic joint inflammation may contribute to osteoarthritis (OA).